Odpowiedzi

2010-02-17T19:43:01+01:00
A)
{ 2x - y = -6
{ -x + y = 2

2x-y-x+y=-6+2
x=-4

-(-4)+y=2
4+y=2
y=-2

1 2 1
2010-02-17T19:43:49+01:00
A) 2x-y= -6
-x+y=2 /*2

2x-y= -6
-2x+2y=4

y= -2

b) 4x-y=5 /* (-2)
10x-2y=11

-8x+2y= -10
10x-2y=11

2x= 1
x=0,5

c) 2x+y = 1
x-y = 5 /* (-2)

2x+y= 1
-2x+2y= -10
3y= -9
y= -3


d) 2x - 3y = 12
x + 3y = 6

3x=18
x=6
y=0



Najlepsza Odpowiedź!
2010-02-17T19:45:06+01:00
A)
{ 2x - y = -6
{ -x + y = 2

x=-4
y=-2

b)
{ 4x - y = 5
{ 10 x -2y = 11

-2x=-1
x=1/2
y=-3

c)
{ 2x + y = 1
{ x - y = 5

3x=6
x=2
y=-3

d)
{ 2x - 3y = 12
{ x + 3y = 6

3x=18
x=6
y=0